Applying XML signatures to the definition of an XML schema for digital ballots - Devegili, Augusto Jun; Tobar Neto, Heres Edison Valdivieso (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2002: Anais do II Workshop em Segurança de Sistemas ComputacionaisDO - 10.5753/sbseg.2002.21258, 2002)
This article presents the definition of an XML schema of digital ballots for official elections using XML signature, thus defining the syntax of the digital ballot and providing the services of identification, integrity and non-repudiation of the ballot. The proposed schema was validated in regard to the XML Schema standard and an application was developed in order to allow the configuration of digital ballots for official elections.